2010
DOI: 10.11646/zootaxa.2514.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Scinax Wagler (Anura: Hylidae) from Cerrado of Brazil

Abstract: A new species of Scinax of central Brazil, closer to the Scinax maracaya (Cardoso & Sazima), from the Cerrado biome (open formations) is described. This new species is characterized by the following combination of traits: moderate size (males 28.4–30.8 mm snout vent length); presence of several flash orange-yellowish transversal stripes on thigh; vocal sac well developed; snout acuminate in profile; advertisement call with one note, 4–15 pulses, and dominant frequency 2.93–3.27 kHz. Description of the adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
2
0
4
Order By: Relevance
“…Scinax is currently the largest genus in the family Hylidae with 112 recognized species (Frost, ; Lourenço et al ., ), and more new species are being described frequently (e.g. 14 new species described in the last three years: Cardoso & Pombal, ; Lourenço, Nascimento & Pires, ; Faivovich, Gasparini & Haddad, ; Nunes, Carvalho & Pereira, ; Nunes & Pombal, , ; Pombal et al ., , ; Cruz, Nunes & De Lima, ; De Lima, Cruz & de Azevedo, ; Silva & Alves‐Silva, ; Lacerda, Peixoto & Feio, ; Nunes, Kwet & Pombal, ). The last phylogenetic assessment of this genus revealed two main clades, the Scinax catharinae clade, including the S. catharinae and Scinax perpusillus groups, and the Scinax ruber clade, including the Scinax rostratus and Scinax uruguayus groups, and 43 species not being assigned to any of the previous groups (Faivovich et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Scinax is currently the largest genus in the family Hylidae with 112 recognized species (Frost, ; Lourenço et al ., ), and more new species are being described frequently (e.g. 14 new species described in the last three years: Cardoso & Pombal, ; Lourenço, Nascimento & Pires, ; Faivovich, Gasparini & Haddad, ; Nunes, Carvalho & Pereira, ; Nunes & Pombal, , ; Pombal et al ., , ; Cruz, Nunes & De Lima, ; De Lima, Cruz & de Azevedo, ; Silva & Alves‐Silva, ; Lacerda, Peixoto & Feio, ; Nunes, Kwet & Pombal, ). The last phylogenetic assessment of this genus revealed two main clades, the Scinax catharinae clade, including the S. catharinae and Scinax perpusillus groups, and the Scinax ruber clade, including the Scinax rostratus and Scinax uruguayus groups, and 43 species not being assigned to any of the previous groups (Faivovich et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although Camera et al depicted this note in their advertisement call figures, they did not mention it in the text, which indicates that they probably misinterpreted it as being part of the advertisement call. Some studies have also reported other species of Scinax which may emit aggressive calls shortly after the advertisement call (e.g., Drummond et al 2007;Bang et al 2017;Lopes et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Estados Alagoas, Bahia, Ceará, Minas Gerais, Paraíba, Pernambuco, Rio Grande do Norte, Sergipe Biomas Caatinga, Mata Atlântica Bacias Hidrográficas Sub-bacia Contas, Sub-bacia Itapecuru-Paraguaçu, Sub-bacia Jaguaribe, Sub-bacia Jequitinhonha, Sub-bacia Litoral AL PE PB, Sub-bacia Litoral CE PB, Sub-bacia Litoral SE, Sub-bacia Paraíba, Sub-bacia Piranhas, Sub-bacia São Francisco Baixo, Sub-bacia São Francisco Médio, Sub-bacia São Francisco Submédio -Hyla pickeli Lutz & Lutz, 1938 Distribuição Endêmica do Brasil: Sim Scinax pachycrus é endêmica do Brasil e apresenta ampla distribuição,com registros em quase todos estados da região Nordeste e no norte de Minas Gerais (Bokermann, 1966;Lutz, 1973;Feio & Caramaschi, 2002;Juncá, 2006;Nunes et al, 2010;Pombal Jr. et al, 2011;Silva et al, 2013;Barbosa & Alves, 2014;Carvalho-e-Silva et al, 2015). Sua extensão de ocorrência é de 583.665 km², obtida via mínimo polígono convexo a partir dos pontos de registro.…”
Section: Distribuição Globalunclassified

Ficha de Scinax pachycrus

Rogério Pereira Bastos,
Marcio Roberto Martins,
Carlos Eduardo Guidorizzi
et al. 2023
Datasets - Sistema SALVE - ICMBio